Struktur dan Komposisi Hutan Mangrove di Kampung Sakartemin Distrik Fakfak Tengah, Kabupaten Fakfak, Papua Barat - Gail Watofa; Ning S. Astuti; Amadion Andika Wanaputra (Jurnal Biologi Papua, 2021)
Sakartemin is one of the village Fakfak Regency which has naturally growing mangrove forest. However, due to the economic development, the government should build up some infrastructures near by those mangrove forest. The disturbance nearby mangrove ecosystem cause changes in structure and composition of mangrove vegetation. This study aims to identify the types of mangrove vegetation and to find out the structure and composition of mangrove forest in Sakartemin Village, Central Fakfak District, Fakfak Regency. The method that used in this study is vegetation survey method combining path and checkered line method. The result shown that mangrove species in the sakartemin village consist of 5 families, namely: Rhizophoraceae, Meliaceae, Soneratiaceae,  Pandanaceae, and Myrsinaceae which consists of 7 species namely: Rhizophora stylosa, R. apiculata, Xylocarpus granatum, Soneratia alba, Bruguiera gymnhoriza, Pandanus sp., and Aegiceras corniculatum. At the seedling level found 1002 individuals, sapling level found 404 individuals, and tree level found 319 individuals. The highest importance value index (IVI) at seedling level was R. stylosa 55.41% and the lowest was A. corniculatum 9.49%. The highest IVI at sapling level was R. apiculata 57.72% and the lowest was Pandanus 5.49%. The highest IVI at the tree level was R. apiculata 88.62% and the lowest was B. gymnhoriza 42.45%.Key words: Sakartemin village; mangrove; structure; composition; Fakfak.